2013
DOI: 10.4172/jpb.1000291
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Study of Human Merkel Cell Carcinoma

Abstract: Merkel Cell Carcinoma (MCC) is an aggressive neuroendocrine cancer of the skin. The incidence has been quadrupled with a 5-year mortality rate of 46%, presently there is no cure for metastatic disease. Despite the contribution of Merkel cell polyomavirus, the molecular events of MCC carcinogenesis are poorly defined. To better understand MCC carcinogensis, we have performed the first quantitative proteomic comparison of formalin-fixed, paraffin-embedded (FFPE) MCC tissues using another neuroendocrine tumor (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Heightened expression of LDHB may contribute to tumor acidity, and growth (24) known to occur in parallel to activated RTK-PI3K-AKT-mTOR signaling (25) and is observed in various types of cancer including bladder (26) merkel cell carcinoma (27) lung cancer (28) glioma (29) or maxillary sinus squamous cell carcinoma, most reporting its association with poor survival rates (30). …”
Section: Discussionmentioning
confidence: 99%
“…Heightened expression of LDHB may contribute to tumor acidity, and growth (24) known to occur in parallel to activated RTK-PI3K-AKT-mTOR signaling (25) and is observed in various types of cancer including bladder (26) merkel cell carcinoma (27) lung cancer (28) glioma (29) or maxillary sinus squamous cell carcinoma, most reporting its association with poor survival rates (30). …”
Section: Discussionmentioning
confidence: 99%
“…The oncogenic property of the large T antigen is via its capability to bind RB1 tumour suppressor gene 65. A quantitative proteomics study by Shao et al 84 showed dysregulation of MAPK, PI3K/AKT/mTOR, Wnt and apoptosis signalling pathways in MCC. LDHB and hnRNPFm, two downstream molecules of the mTOR pathway, are frequently overexpressed in MCC, and AKT phosphorylation determined by IHC occurs in 88% of MCC cases 84.…”
Section: Molecular/immunohistochemical Studies With Possible Therapeumentioning
confidence: 99%
“…A quantitative proteomics study by Shao et al 84 showed dysregulation of MAPK, PI3K/AKT/mTOR, Wnt and apoptosis signalling pathways in MCC. LDHB and hnRNPFm, two downstream molecules of the mTOR pathway, are frequently overexpressed in MCC, and AKT phosphorylation determined by IHC occurs in 88% of MCC cases 84. Among MCCs with PIK3CA mutations, 2/2 (100%),77 1/7 (14%)66 and 1/3 (33.3%)69 tumours were reported to be MCPyV-positive.…”
Section: Molecular/immunohistochemical Studies With Possible Therapeumentioning
confidence: 99%
“…An important study used LCM and proteomic analysis to demonstrate that the CD21 EBV receptor was only expressed on tonsil epithelial cells (71). A quantitative proteomic analysis of Merkel Cell carcinoma indicated that the MAPK, PI3K/Akt/mTOR, Wnt, and apoptosis signaling pathways were involved in the development of the tumor (72). As mass spectrometry techniques become more sensitive, studies such as these will be able to use proteomics to gain direct information about infection and disease states.…”
Section: Molecular and Cellular Proteomics 16 Supplement 4 S67mentioning
confidence: 99%